Analisa Kehilangan Hasil Produksi Usahatani Kentang - Drajat, Luthfi Zakaria; Noor, Trisna Insan; Rachmawati, Erna; Saidah, Zumi (Universitas Galuh, 2025)
Potatoes is known to have good prospects and potential to be developed in order to spur food diversification programmes. Potato production in Indonesia is increased by an average approximately around 2.34% each year. Garut Regency is one of the district in West Java Province that produces potatoes in Indonesia. One of the areas in Garut that produces potatoes is Sarimukti Village. However, potato production in Garut Regency experiences fluctuations in production due to food loss in potato farming. This research aims to find out how much is food loss in potato farming and the causes of food loss as well as farmers characteristics that influence the food loss in Sarimukti Village, Pasirwangi District, Garut Regency. This research uses the quantitative descriptive method with interview and observation techniques to 55 farmers. Results The results showed that there was a loss of potato yield with an average of 2091,8 kg/ha at the production level. Moreover, there is an influence between the production factors used by Sarimukti Village farmers and the potato yield loss that occurs.potato yield loss that occurs.